Influence of the regulatory peptide galanin on cytokine expression in human monocytes. Issue 1 (10th May 2019) - Ramspacher, Andrea; Neudert, Magdalena; Koller, Andreas; Schlager, Sandra; Kofler, Barbara; Brunner, Susanne Maria
Abstract: Current research into neuropeptides is bringing to light many remarkable functions of these endocrine/neurocrine/paracrine factors, such as their roles in modulating immune responses. Galanin is a neuropeptide expressed in both neural and non‐neural tissues and exerts its effects through three G protein–coupled receptors, GAL1, 2, 3 ‐R. It has been demonstrated that galanin has modulatory effects on immune cells, including neutrophils and natural killer cells. Because monocytes express GAL2 ‐R, and therefore are expected to be a target of galanin, we analyzed the effect of galanin on the expression of cytokines and chemokines by monocytes. Galanin increased the expression of IL‐1β up to 1.5‐fold, TNF‐α, IL‐10, IL‐18, and CCL3 up to twofold, and CXCL8 up to fourfold in nonactivated monocytes, but had no major effect on activated monocytes. A cross‐correlation analysis of cytokine expression profiles, irrespective of the activation status of the monocytes, revealed that galanin changed the cross‐correlation of the expression of certain cytokines. Galanin abolished several significant correlations in IFN‐γ–stimulated monocytes. For example, treatment with 10 nM galanin changed the Spearman's rank coefficient of IL‐18 and CXCL8 from 0.622 ( P  ≤ 0.01) to 0.126. These results further emphasize the importance of neuroregulatory peptides, such as galanin and their therapeutic potential to treat inflammatory diseases. Abstract : Neuropeptides have various functions, including modulating immune responses. Because monocytes express one of the receptors for the neuropeptide galanin, the authors analyzed the effect of galanin on the expression of cytokines and chemokines by monocytes. Their data indicate that galanin modulates the immune responses of monocytes by regulating cytokine expression networks and that it exerts different functions in naive and inflammation‐induced cells.